The Effect of Work Stress on Work Deviant Behavior Case Study: CV. Madinna Dome Ambassador through Job Satisfaction as an Intervening Variable - Komarudin, Diwa Ghulam Fajrin; Astuty, Isthofaina (Journal of Business Management and Islamic Banking, 2023)
Research Aims: This study aims to analyze the effect of work stress on work deviant behavior case studies in CV. Duta Madinna Kubah through Job Satisfaction as an intervening variable. Methodology: This study used a sample of 95 respondents who were determined by the sampling technique with the census method. In this study, using data analysis techniques, namely Path Analysis (path analysis). The analytical tool used in this study using SPSS software. Research Findings: The results of this study indicate that the variable job stress has a significant negative effect on job satisfaction, job satisfaction has a negative and significant effect on work deviant behavior, job stress has a significant positive effect on work deviant behavior, job stress has a significant effect on work deviant behavior, which is mediated by the variable job satisfaction. Theoretical Contribution: This research advances theoretical understanding by revealing the complex interaction among work stress, job satisfaction, and deviant work behavior, providing valuable insights for academics and practitioners in the field of organizational psychology and management. Implication: Organizations can implement training programs to equip employees and managers with effective stress management strategies. Additionally, organizational development efforts can include initiatives to enhance job satisfaction and foster a positive work culture.